Tingkat Kesejahtaraan Masyarakat Desa Sari Tani Sebagai Desa Penyangga Kawasan Suaka Margasatwa Nantu-Boliyohuto - Rahmat Biki; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
It is essential to involve communities in the surrounding areas or buffer zones towards effective and efficient forest area management in the management of forest conservation areas. As one of the supporting villages in the Nantu-Boliyohuto Wildlife Sanctuary area, Sari Tani Village is located in the Wonosari sub-district, Boalemo Regency, which needs to be a part of a collaboration or partner in sustainable forest management. Therefore, the community's welfare in the buffer village should be a common concern as a manifestation of the vision of sustainable forest management. Accordingly, this research seeks to measure the welfare level of the community in the village. The data were generated from interviews and observations on 85 families as research samples. Those were further analyzed using descriptive, qualitative, and quantitative methods, referring to eight welfare indicator criteria based on the Central Bureau of Statistics (BPS 2016) with weighting or scoring. The results indicated that the score of the welfare indicator assessment was 13. It means that the welfare level of the Sari Tani village community was in the low category number interval. Thus, it is suggested to develop the village area as the smallest government administration area and as a buffer village for the Nantu-Boliyohuto wildlife sanctuary area using an approach to indicators that affect the level of welfare, viz. education, employment, levels and patterns of consumption, and poverty.